2008
DOI: 10.4049/jimmunol.181.4.2513
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 1 Regulates a Critical Checkpoint for Autoimmune Myocarditis and Pneumonitis in MRL Mice

Abstract: MRL/MpJ-Faslpr (MRL-Faslpr) mice develop a spontaneous T cell and macrophage-dependent autoimmune disease that shares features with human lupus. Interactions via the programmed death 1/programmed death ligand 1 (PD-1/PD-L1) pathway down-regulate immune responses and provide a negative regulatory checkpoint in mediating tolerance and autoimmune disease. Therefore, we tested the hypothesis that the PD-1/PD-L1 pathway suppresses lupus nephritis and the systemic illness in MRL-Faslpr mice. For this purpose, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
124
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 42 publications
6
124
0
Order By: Relevance
“…This is consistent with reports that tissue expression of B7-H1 tolerize infiltrating T cells in the lung and other peripheral organs. 46,47 This finding provides a likely answer to questions brought up by Burman and colleagues regarding an IFN-␥-induced unknown protective mechanism possessed by the host tissues. 21 Furthermore, we observed that all GVHD target tissues could up-regulate expression of B7-H1 in an IFN-␥-dependent manner and that tissue expression of B7-H1 also played an important role in ameliorating Th1-mediated GVHD tissue damage in gut and liver (Yi T, Zeng D, unpublished observation).…”
Section: Discussionmentioning
confidence: 61%
“…This is consistent with reports that tissue expression of B7-H1 tolerize infiltrating T cells in the lung and other peripheral organs. 46,47 This finding provides a likely answer to questions brought up by Burman and colleagues regarding an IFN-␥-induced unknown protective mechanism possessed by the host tissues. 21 Furthermore, we observed that all GVHD target tissues could up-regulate expression of B7-H1 in an IFN-␥-dependent manner and that tissue expression of B7-H1 also played an important role in ameliorating Th1-mediated GVHD tissue damage in gut and liver (Yi T, Zeng D, unpublished observation).…”
Section: Discussionmentioning
confidence: 61%
“…In previous studies, PD-L1 chimeric mice that expressed PD-L1 only on hematopoietic cells of the heart showed an accelerated, early graft rejection after heart transplantation, whereas the expression of PD-L1 on non-hematopoietic cells of the heart led to a delayed rejection. These data indicate that PD-L1 expression on nonhematopoietic cells plays a significant role in regulating transplantation immune responses [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…B7-H1 and B7-DC act as inhibitory costimulatory ligands by binding to their common receptor, programmed death-1 (PD-1), which is expressed on activated but not on resting T cells (Freeman et al, 2000). Involvement of the PD-1 pathway in peripheral tolerance is suggested in PD-1-deficient mice that develop a lupus-like autoimmune disease (Nishimura et al, 1999) and autoimmune dilated cardiomyopathy (Lucas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%